Public Infrastructure and Economic Growth in the Local Region - Nairobi Nairobi; Riana Respitasari (Jurnal Ekonomi Pembangunan, 2021)
This study aims to analyze the effect of public infrastructure on economic growth in Lampung Province. The data used are time series and cross sections for the period 2012-2018 and 14 districts/cities. The method applied is the panel data model with the random effect model method. The results showed that Infrastructure, Irrigation Infrastructure, Health Infrastructure, Investment, Labor, and Gini Growth had a significant and positive effect on economic growth, while capital expenditures insignificant effect on economic growth. The implications of these findings indicate that public sector investments such as road infrastructure, bridges and other infrastructure facilities are important.